A STUDY OF LYCIUM BARBARUM POLYSACCHARIDES (LBP) EXTRACTION TECHNOLOGY AND ITS ANTI-AGING EFFECT - Yi, Ran; Liu, Xiao-min; Dong, Qi (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The objective of the study was to optimise the LBP extraction technology and to study the anti-aging effect of LBP by establishing D-gal aging mouse model. Orthogonal design was used to study the extraction technology The experimental aging mouse model was formed by continuous injection of D-gal, and the anti-aging capacity of LBP was tested using measuring MDA, CAT and GSH-px contents and SOD activity in blood and SOD, MDA and Hyp levels in skin. The results showed that the optimum LBP extraction option determined by the orthogonal design is as follows: solid-liquid ratio of 1:30, extraction for 2 times, 90 min each time, and power is 100 kHz. Thus, LBP can increase SOD, CAT and GSH-px levels in blood and reduce MDA level. It can also improve skin SOD activity, reduce skin MDA content, and increase Hyp content. We concluded that the extraction method established in this experiment is easy and feasible, and the yield of LBP is high, apparently showing that LBP has the potential of delaying senility in D-gal induced mice.